2022
DOI: 10.15294/sji.v9i2.35149
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Classification Algorithms for Cyberbullying Crime Detection: An Experimental Study of Twitter Social Media in Indonesia

Abstract: Purpose: This research aims to identify content that contains cyberbullying on Twitter. We also conducted a comparative study of several classification algorithms, namely NB, DT, LR, and SVM. The dataset we use comes from Twitter data which is then manually labeled and validated by language experts. This study used 1065 data with a label distribution, namely 638 data with a non-bullying label and 427 with a bullying label.Methods: The weighting process for each word uses the bag of word (BOW) method, which use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The hate speech that is expressed is often inseparable from SARA (tribe, religion, race and inter-group) motives. This statement is said because it shows that users use the Twitter social media platform to convey ideas, criticize, disseminate information quickly and have arguments between people [8]- [11]. fellow social media users.…”
Section: Introductionmentioning
confidence: 99%
“…The hate speech that is expressed is often inseparable from SARA (tribe, religion, race and inter-group) motives. This statement is said because it shows that users use the Twitter social media platform to convey ideas, criticize, disseminate information quickly and have arguments between people [8]- [11]. fellow social media users.…”
Section: Introductionmentioning
confidence: 99%
“…This study seeks to address this gap by comparing the performance of SVM and Random Forest (RF) algorithms in hoax analysis on Twitter. SVM and RF were chosen due to their excellent performance in text mining [8], [9], [11], [18]. The study's contribution is twofold: first, it scientifically evaluates the performance of SVM and RF for hoax analysis, and second, it offers practical recommendations on government policy regarding the capital relocation.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method uses a dataset of 1053 comments on Instagram, which obtains an accuracy of 79%. Then, Muzakir et al [14] also detect cyberbullying using a Support Vector Machine (SVM) and Bag of Words (BoW) as feature extraction. They reported that the accuracy score is 76% using a dataset from Twitter with 1065 tweets.…”
Section: Introductionmentioning
confidence: 99%